2020
DOI: 10.3389/fimmu.2020.00029
|View full text |Cite
|
Sign up to set email alerts
|

CD44 Loss Disrupts Lung Lipid Surfactant Homeostasis and Exacerbates Oxidized Lipid-Induced Lung Inflammation

Abstract: Alveolar macrophages (AMs) are CD44 expressing cells that reside in the alveolar space where they maintain lung homeostasis by serving critical roles in immunosurveillance and lipid surfactant catabolism. AMs lacking CD44 are unable to bind the glycosaminoglycan, hyaluronan, which compromises their survival and leads to reduced numbers of AMs in the lung. Using RNA sequencing, lipidomics and multiparameter flow cytometry, we demonstrate that CD44 −/− mice have impaired AM lipid homeostasis and increased surfac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 53 publications
1
30
0
Order By: Relevance
“…Studies show that CD44 deficiency increased lipid accumulation in alveolar macrophages (AMs) and increased surfactant lipids, resulting in impaired lung lipid homeostasis [57]. Transcriptome data from CD44-deficient AMs revealed that cd44 ablation affected lipid homeostasis through a variety of pathways, including sterol/cholesterol synthesis and protein phosphorylation-related signalling pathways.…”
Section: Lipid Metabolism In Other Cellsmentioning
confidence: 99%
“…Studies show that CD44 deficiency increased lipid accumulation in alveolar macrophages (AMs) and increased surfactant lipids, resulting in impaired lung lipid homeostasis [57]. Transcriptome data from CD44-deficient AMs revealed that cd44 ablation affected lipid homeostasis through a variety of pathways, including sterol/cholesterol synthesis and protein phosphorylation-related signalling pathways.…”
Section: Lipid Metabolism In Other Cellsmentioning
confidence: 99%
“…Alveolar macrophages express the hyaluronan receptor CD44 and thus are coated with bound hyaluronan promoting their survival [50]. Moreover, alveolar macrophages lacking CD44 have impaired lipid homeostasis leading to an increase in intraalveolar surfactant lipids [51]. This indicates an important role for hyaluronan in surfactant catabolism.…”
Section: Interactions Between Surfactant and The Glycocalyxmentioning
confidence: 99%
“…We regularly observed these structures to be in direct contact with the glycocalyx on top of the plasma membrane. Previous work studying interactions between surfactant and specific glycocalyx components has been limited to the proteoglycan hyaluronan ( Lu et al, 2005 ; Taeusch et al, 2005 ; Wang et al, 2006 ; Lopez-Rodriguez et al, 2013 ; Dong et al, 2020 ). By combining MGE and EM, we found the extracellular lamellar structures to be enriched in sialic acids ( Figure 5 ).…”
Section: Discussionmentioning
confidence: 99%